Japanese Disaster Cinema as Lessons Learned in Disaster Education in Indonesia - Wuryantari, Benedicta Ayu Indiwara; Kurniadi, Anwar; Subiyanto, Adi (Cita konsultindo, 2026)
This study aims to systematically review the development of studies on Japanese disaster cinema and identify its implications for the development of disaster education in Indonesia. The study uses a qualitative approach through a systematic literature review (SLR) following the PRISMA-based selection process. Literature was collected from international academic databases and analyzed using thematic analysis to identify patterns of meaning and trends in studies. The result of the study show that research on Japanese disaster cinema developed dynamically in the period 2012-2025 and can be classified into four main themes. The first theme relates to disaster narratives and social meaning construction, which positions film as a medium for reflecting on trauma, risk, and social charge. The second theme highlights trauma and collective memory, where cinema functions as a cultural archive that records and negotiates post-disaster experiences. The third theme discusses the relationship between humans, nature, and technology, showing how cinema represents disasters as the result of complex interactions between ecological systems, modernity, and human responsibility. The fourth theme examines the implications of cinema as a pedagogical medium capable of bridging the cognitive and affective dimensions of disaster education. The research findings confirm that cinema not only functions as a cultural representation, but also as a space for social reflection and learning that has the potential to increase risk literacy, social empathy, and critical awareness. Therefore, the use if visual media and cinematic narratives can be a complementary approach in the development of more contextual, participatory, and culture-based disaster education in Indonesia.